Heart full of burden - Seshan, T. (New Delhi, 1995)
Ever ver since T.N. Seshan donned the mantle of the Chief Election Commissioner, Indian politics has never been the same again. His virtual one-man crusade against corruption in elections has attained legendary proportions. Every action of Seshan seems to stir up a hornet's nest. His determined attempts to clean up the electoral "Augean stables" have started yielding results. The entire gamut of election campaigns has undergone a sea-change, largely due to one individual's never-say-die efforts. All brands of politicians take Seshan's decrees seriously, however loftily they may be perched. Consequently, whenever Seshan addresses public gatherings, in his own inimitably pungent style, his words make a profound impact, compelling the audience to ponder, understand and analyse their content. This volume brings together an enthralling collection of Seshan's addresses, which cover a diverse range of topics and are dotted with flashes of wry, self-deprecating humour. Seshan. who is moulded in a "no-punches-pulled" frame, hits out at politicians, bureaucrats, goonda elements, communalists and. at the same time, expresses his deep concern and respect for democratic values, integrity in public life, public accountability and. above all, the noble Constitution of India. And running through the entire multitude of words is a deep and disturbing sense of one man's agony at the nation's present condition.
Keywords: Election Commissioner-India